The use of gentamicin-polymethylmethacrylate (Septopal) beads and chains in the treatment of pyogenic bone and soft tissue infection - Barquet, Antonio (Cirugía del Uruguay, 1982)
The authors present the initial experience in the treatment of pyogenic infection of bone and soft issue by means of necrectomy and the implantation of gentamycin PMMA chains and pearls. lnfection was controlled in more than 75% of a consecutive series of 25 obsevations; and having in mind that these are the first cases where the new procedure was performed, with inherent technical defects, the control can be considered as of high efficacy.